2019
DOI: 10.1186/s12919-019-0180-y
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic approach for differentiating abdominal tuberculosis from ovarian malignancy: a case series and literature review

Abstract: Background: Abdominal tuberculosis is an uncommon variant of extrapulmonary tuberculosis. It accounts for 3.5% of extrapulmonary tuberculosis. Diagnosis of abdominal tuberculosis is still a challenge due to its non-specific symptoms. Abdominal tuberculosis and ovarian cancer may show similar symptoms, laboratory and imaging features. The goal of our report is to emphasize for the need of a diagnostic approach based on clinical manifestations, laboratory, imaging findings, and additional tests for considering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
8
0
2
Order By: Relevance
“…ADA is a purine degrading enzyme that is essential for T lymphocyte proliferation and differentiation, a process that is necessary for the immune response against M tuberculosis. T-cell-based interferon gamma release assay (IGRA) is another non-invasive test that could be used as a substitute for tuberculin skin test [18] [2] . In 1 study, IGRA was found to have sensitivity between 72-90% and specificity between 68%-82% [18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADA is a purine degrading enzyme that is essential for T lymphocyte proliferation and differentiation, a process that is necessary for the immune response against M tuberculosis. T-cell-based interferon gamma release assay (IGRA) is another non-invasive test that could be used as a substitute for tuberculin skin test [18] [2] . In 1 study, IGRA was found to have sensitivity between 72-90% and specificity between 68%-82% [18] .…”
Section: Discussionmentioning
confidence: 99%
“…T-cell-based interferon gamma release assay (IGRA) is another non-invasive test that could be used as a substitute for tuberculin skin test [18] [2] . In 1 study, IGRA was found to have sensitivity between 72-90% and specificity between 68%-82% [18] . While having lower sensitivity and specificity than ADA, IGRA is sometimes used first as it doesn't require an invasive procedure to obtain ascitic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no available classification to determine the degree of abdominal tuberculosis extension that resembles ovarian mass. Therefore, we tried to arrange a scoring system based on previous studies regarding abdominal TB characteristics [6,[10][11][12][13]. The lowest score was 4, which was included in mild degree category, and the highest score was 13, which was included in severe degree category.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of abdominal TB extent from abdominal CT-scan findings with contrast was classified based on previous studies and had been published and used the following scoring system: • Mild, if the score is between 5-8 • Moderate, if the score is between 9-12 • Severe, if the score is more than 12 [6,[10][11][12][13]].…”
Section: Data Collectionmentioning
confidence: 99%
“…It allows not only inspection of peritoneum, but also obtaining specimens for histology with lower risk of surgical morbidity. 15,24 Positive appearance of TB in 96% of cases 6 . This includes scattered or confl uent multiple, whitish, miliary nodules (<5 mm) over the visceral and parietal peritoneum, adhesion, thickened and hyperemic peritoneum, and turbid ascites.…”
Section: Discussionmentioning
confidence: 99%